Loss of the Major Phosphatidylserine or Phosphatidylethanolamine Flippases Differentially Affect Phagocytosis - Fazeli, Gholamreza; Beer, Katharina B.; Geisenhof, Michaela; Tröger, Sarah; König, Julia; Müller-Reichert, Thomas; Wehman, Ann M. (Frontiers in Cell and Developmental Biology, 2020)
The lipids phosphatidylserine (PtdSer) and phosphatidylethanolamine (PtdEth) are normally asymmetrically localized to the cytosolic face of membrane bilayers, but can both be externalized during diverse biological processes, including cell division, cell fusion, and cell death. Externalized lipids in the plasma membrane are recognized by lipid-binding proteins to regulate the clearance of cell corpses and other cell debris. However, it is unclear whether PtdSer and PtdEth contribute in similar or distinct ways to these processes. We discovered that disruption of the lipid flippases that maintain PtdSer or PtdEth asymmetry in the plasma membrane have opposite effects on phagocytosis in Caenorhabditis elegans embryos. Constitutive PtdSer externalization caused by disruption of the major PtdSer flippase TAT-1 led to increased phagocytosis of cell debris, sometimes leading to two cells engulfing the same debris. In contrast, PtdEth externalization caused by depletion of the major PtdEth flippase TAT-5 or its activator PAD-1 disrupted phagocytosis. These data suggest that PtdSer and PtdEth externalization have opposite effects on phagocytosis. Furthermore, externalizing PtdEth is associated with increased extracellular vesicle release, and we present evidence that the extent of extracellular vesicle accumulation correlates with the extent of phagocytic defects. Thus, a general loss of lipid asymmetry can have opposing impacts through different lipid subtypes simultaneously exerting disparate effects.